Spontaneous retroperitoneal bleeding from rupture of a massive renal angiomyolipoma managed with transcatheter arterial embolization - Majd Oweidat, MD; Mohammed Alra'e, MD; Ammar W․ M․ Hassouneh, MD; Besan Sarahna, MD; Ibrahim Kattoush, MD (Radiology Case Reports, 2025)
Ruptured renal angiomyolipoma (AML) is a rare but potentially life-threatening condition requiring prompt diagnosis and intervention. We report the case of a young female who presented with acute left-sided abdominal pain and gross hematuria. She had a known diagnosis of a large left renal AML. Initial evaluation revealed stable vital signs and mild anemia. Contrast-enhanced computed tomography (CT) confirmed a ruptured AML with an associated hematoma but no active extravasation. The patient was admitted for conservative management and subsequently underwent transcatheter arterial embolization (TAE) 2 weeks later. Under ultrasound guidance, vascular access was obtained via the right common femoral artery, and superselective catheterization of the feeding arteries to the tumor was performed. Embolization was achieved using a Lipiodol–N-butyl cyanoacrylate (NBCA) glue mixture in a 1:5 ratio. Final angiography showed complete devascularization of the lesion. Follow-up contrast-enhanced CT showed hematoma resolution, reduced tumor size, and no evidence of residual bleeding or nontarget embolization. The patient experienced marked clinical improvement and remained stable on follow-up without recurrence of symptoms. This case highlights the importance of considering renal AML in the differential diagnosis of spontaneous retroperitoneal hemorrhage. It also demonstrates the value of imaging in diagnosis and follow-up, as well as the role of TAE as an effective intervention in selected cases while preserving renal function.